PROCESSES IN ETHNO-CULTURAL SYNCRETICS AND VIEWS ON INCULTURATION (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the manifestations of ethnocultural syncretic processes and views on inculturation in it are revealed in a scientific-analytical, scientific-discussive way. In this, the features, important signs and social significance of ethnocultural syncretic processes are expressed in a scientific-analytical way. It is also pointed out that syncretic phenomena of ethnos sometimes occur as inculturation.